Answers

  • Brainly User
2016-07-11T13:02:06+08:00
3t² = 12
3t²/3 = 12/3
t² = 4
√t² = √4
t = +2,  -2

Check: 
t = 2                                       t = -2
3(2)² = 12                              3(-2)² = 12
3(4) = 12                                3(4) = 12

3r² = 18
3r²/3 = 18/3
r² = 6
√r² = √6
r = +√6,  -√6

Check:
r = +√6                              r = -√6
3(+√6)² = 18                      3(-√6)² = 18 
3(6) = 18                            3(6) = 18

x² = 9/16
√x² =  \sqrt{ \frac{9}{16} }
x = 3/4,  -3/4

Check:
(3/4)² = 9/16
9/16 = 9/16

(-3/4)² = 9/16
9/16 = 9/16
0